Contemporary Masculinities in the UK and the US : Between Bodies and Systems - Horlacher, Stefan; Floyd, Kevin (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book is about ways to understand masculinity as systemic and corporeal, structural and performative all at once. It argues that the tension between an understanding of "masculinity" in the singular and "masculinities" in the plural poses a problem that can better be understood in relation to a concomitant tension: between systems on the one hand, and bodies on the other - between abstract structures such as patriarchy, kinship or even language, and the various concrete forms taken by gendered, individuated corporeality. The contributions collected here investigate how masculinities become apparent, how they take shape and what systemic functions they have. What, they ask, are the relations between the abstract and corporeal, metaphorical and metonymic manifestations of masculinity? How are we to understand masculinity as a simultaneously systemic and corporeal, performative concept? .
Keywords: Social sciences.; Ethnology -- Europe.; Sociology.; Sex (Psychology).; Gender expression.; Gender identity.; elektronické knihy; electronic books